Research on intelligent cloud native architecture and key technologies for cloud and network integration - Gang LU; Changyi CHEN; Zelong HUANG; Zeyuan HUANG (Dianxin kexue)
Cloud native technology,as the latest technology achievement of cloud computing,promotes internet and enterprise application to cloud.Cloud native technology can provide more economical and convenient deployment and operation methods for communication operator network.With the promotion of cloud and network integration of operators,cloud native is the core technology and key grasp of operators’ network cloud.The application and problems of cloud native technology were analyzed,an intelligent cloud native architecture for cloud and network integration was proposed,evolution design,architecture deployment scheme and key technologies were studied,and cloud native promotion measures were prospected.